2015
DOI: 10.1088/0004-637x/808/1/89
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Gravity Waves by Fingering Convection, and the Formation of Compositional Staircases in Stellar Interiors

Abstract: Fingering convection (or thermohaline convection) is a weak yet important kind of mixing that occurs in stably-stratified stellar radiation zones in the presence of an inverse mean-molecular-weight gradient. Brown et al. (2013) recently proposed a new model for mixing by fingering convection, which contains no free parameter, and was found to fit the results of direct numerical simulations in almost all cases. Notably, however, they found that mixing was substantially enhanced above their predicted values in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 41 publications
2
59
0
Order By: Relevance
“…Several theories have been proposed in the non-rotating case (Stern & Turner, 1969;Radko, 2013). For the moderate values of P r characterising planetary cores, their generation may rely on the mixing by nonlinear internal waves (Garaud et al, 2015). Yet, these mechanisms remain to be confirmed in the presence of rapid rotation.…”
Section: Discussion and Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several theories have been proposed in the non-rotating case (Stern & Turner, 1969;Radko, 2013). For the moderate values of P r characterising planetary cores, their generation may rely on the mixing by nonlinear internal waves (Garaud et al, 2015). Yet, these mechanisms remain to be confirmed in the presence of rapid rotation.…”
Section: Discussion and Improvementsmentioning
confidence: 99%
“…Definition Earth (current) Stars L Lewis κ T /κ C 10 4 10 3 − 10 7 P r Prandtl ν/κ T 0.01 − 0.1 10 −6 Sc Schmidt ν/κ C 10 2 − 10 3 10 −3 − 10 1 Ek Ekman ν/(Ω s R 2 ) 10 −15 10 −18 Table 1: Dimensionless numbers characterising diffusive effects and typical values in the Earth's liquid core (Braginsky & Roberts, 1995;Labrosse, 2015) and stably stratified stellar envelopes (Garaud et al, 2015). Kinematic viscosity ν, thermal diffusivity κ T , compositional diffusivity κ C , planetary angular velocity Ω s and radius R.…”
Section: Symbol Namementioning
confidence: 99%
“…Thus, neither mechanism for staircase formation is present. Having said this, Brown et al [10] and Garaud et al [48] recently discovered that staircases can form in three dimensions even when the flux increases monotonically with the density gradient, although their mechanism also relies on gravity wave generation. In summary, the possibility that the model (in two or three dimensions) captures staircase formation must be kept open, particularly at large Ra, since oceanic staircases are observed in regions with density ratios that are in fact quite small.…”
Section: Discussionmentioning
confidence: 99%
“…These later evolutionary phases are a rich site of fascinating challenges that include the interplay between nuclear burning (Couch et al, 2015;Farmer et al, 2016;Jones et al, 2017;Müller et al, 2016), convection (Meakin and Arnett, 2007;Viallet et al, 2013), rotation (Chatzopoulos et al, 2016;Heger et al, 2000;Rogers, 2015), radiation transport (Jiang et al, 2015(Jiang et al, , 2016, instabilities (Garaud et al, 2015;Wheeler et al, 2015), mixing (Maeder and Meynet, 2012;Martins et al, 2016), waves (Aerts and Rogers, 2015;Fuller et al, 2015;Rogers et al, 2013), eruptions (Humphreys and Davidson, 1994;Kashi et al, 2016;, and binary partners (Justham et al, 2014;Marchant et al, 2016;Pavlovskii et al, 2017). This bonanza of physical puzzles is closely linked with compact object formation by corecollapse supernovae (e.g., Eldridge and Tout, 2004;Özel et al, 2010;Perego et al, 2015;Sukhbold et al, 2016;Suwa et al, 2015;Timmes et al, 1996) and the diversity of observed massive star transients (e.g., Ofek et al, 2014;Smith et al, 2016;Van Dyk et al, 2000).…”
Section: B Helium Burning In Massive Starsmentioning
confidence: 99%